Social Media Influence on Consumer Behavior Insights from Supermarket Shoppers in Lahore - Zafar, Bilal; Younis, Muhammad (Journal of Business and Economic Options, 2020)
With the widespread adoption of social media platforms and advancements in information technology, consumers now have unprecedented access to information and communication channels that influence their purchasing decisions. The study delves into this evolving dynamic by focusing on the Pakistani market, specifically examining consumer behavior in the context of shopping at large supermarkets in Lahore. By adopting a qualitative research approach, the study aims to capture the nuanced perceptions and behaviors of consumers regarding the use of social media and conventional media for obtaining shopping-related information. Through in-depth interviews with participants from diverse backgrounds, the study uncovers valuable insights into how consumers navigate and interact with different media channels in their shopping journey. Participants' perspectives shed light on the increasing significance of social media as a preferred source of information, surpassing traditional forms of media such as television, radio, and print. One of the key findings of the study is the pronounced influence of social media on shaping consumer attitudes, preferences, and purchase decisions. Participants highlight the interactive and immersive nature of social media platforms, which allow them to access real-time reviews, recommendations, and product information from their peers and influencers. Moreover, the study underscores the importance of businesses and marketers understanding and harnessing the power of social media to effectively engage with consumers and drive favorable outcomes. With social media becoming an integral part of consumers' shopping experiences, businesses must adapt their marketing strategies to leverage these platforms' potential for building brand awareness, fostering customer engagement, and driving sales. In light of these findings, the study recommends that businesses in Lahore and beyond prioritize their social media presence and invest in strategies that resonate with their target audience. By leveraging the reach and influence of social media channels, businesses can not only enhance their visibility and reputation but also cultivate meaningful relationships with consumers, ultimately driving positive outcomes for their brands.